If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7nsquared + 7 = 12n Reorder the terms: 7 + 7adenqrsu = 12n Solving 7 + 7adenqrsu = 12n Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 7adenqrsu = -7 + 12n Combine like terms: 7 + -7 = 0 0 + 7adenqrsu = -7 + 12n 7adenqrsu = -7 + 12n Divide each side by '7denqrsu'. a = -1d-1e-1n-1q-1r-1s-1u-1 + 1.714285714d-1e-1q-1r-1s-1u-1 Simplifying a = -1d-1e-1n-1q-1r-1s-1u-1 + 1.714285714d-1e-1q-1r-1s-1u-1
| 2(4x+3)+6= | | -56=88-9x | | 29-7x=28x-28 | | 9+14x+5x=180 | | 7-2f=1.98 | | 10-2y+4x=0 | | -7[4+7(-5+7)]+16= | | 50+3b=134 | | 3(1)=3 | | 7x+6=2z+2 | | 12x-13=-6x | | 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 | | 3l+4-4l=-3 | | 53+18w=c | | 7x-4=37 | | 3(t-3)-2t=-30 | | (2m+3t)(3m-4t)= | | y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 | | 7-3x-(-5x+2)+1+7x=5x | | 2x+4x-9x+7= | | 5(20x+25)=925 | | 10*xy+90=72x | | 12y-5y-7+4= | | 10x-50=7x+1 | | x-(5-2x)=1+(2+x) | | 2+(-3)(4)-(-5)= | | 15=-7+44y | | -100=x^2-29x |